Dietary signals in the premolar dentition of primates. Issue 121 (August 2018) - Scott, Jeremiah E.; Campbell, Ryan M.; Baj, Luisa M.; Burns, Maegan C.; Price, Mia S.; Sykes, Jaime D.; Vinyard, Christopher J.
Abstract: Dietary adaptations specific to the premolar row remain largely undocumented across primates. This study examines how relative premolar size varies among broad dietary groups (i.e., folivores, frugivores, insectivores, hard-object feeders) using a phylogenetically and ecologically diverse sample of species. We quantified relative premolar size with shape ratios computed using mandibular length, body mass, palate area, and M 1 area to evaluate hypotheses that link variation in relative premolar size to differences in tooth loading, energy requirements, the probability of tooth-food-tooth contact during mastication, and shifts in preferred bite point. Our results revealed the following dietary signals. First, primate folivores have large premolar rows relative to palate area in comparison to frugivores and insectivores. This contrast is consistent with the hypothesis that folivores require large postcanine teeth relative to the size of the oral cavity to increase the probability of particle fracture during mastication. Second, hard-object feeders are distinct from other groups in having P 4 s that are large relative to their M 1 s. This morphology is not associated with an increase in the size of the premolar row relative to mandibular length. This combination challenges the idea that hard-object feeders have large premolars as an adaptive response to resisting the loads incurred when processing mechanically challenging foods. We therefore interpret the large P 4 /M 1 ratios of hard-object feeders as indicating greater functional integration across the premolar-molar boundary owing to a mesial shift in preferred bite point. Finally, in a restricted subset of anthropoids, we found that, relative to mandibular length, premolar area increases with dietary elastic modulus ( E ) and toughness ( R ), indicating that relative premolar size is evolutionarily sensitive to food mechanical properties. Thus, our results show that relative premolar size is correlated with diet, highlighting the importance of this region for understanding the evolutionary history of primate dietary adaptations.